Medicinal plant diversity and uses in the Sango bay area, Southern Uganda - Ssegawa, Paul; Massan Kasenene, John (Journal of ethnopharmacology, 2007)
An inventory is presented for the medicinal plants of the Sango bay area in Southern Uganda. Fieldwork was conducted between March and August 2004, using semi-structured interviews, questionnaires and participant observation as well as transect walks in wild herbal plant collection areas. One hundred and eighty-six plant species belonging to 163 genera and 58 families with medicinal values were recorded. Remedies from these plants are prepared mainly as decoctions and infusions and administered in a variety of ways. The majority (51.3%) of these plants are herbaceous, growing mainly in the wild. Grasslands provided the highest number of species for medicinal use (54.6%) followed by home gardens (25.4%) and fallow land (19.5%). A review of Ugandan and other literature indicated that 72 (38.5%) medicinal plants reported in this study have not been reported previously as having medicinal value. According to respondents, plant species including Hallea rubrostipulata (K. Schum) J-F Leroy (Rubiaceae) and Warburgia ugandensis Sprague (Canellaceae) are threatened because of poor harvesting techniques and unsustainable harvesting intensities. Suggestions for future conservation programs, sustainable utilization and ethnopharmacological studies are given.
Keywords: Medicinal plants use; Over-exploitation; Indigenous knowledge; Uganda